In vivo Pharmacokinetics and Toxicity Profile of the Anti-HIV Agent Stampidine in Dogs and Feline Immunodeficiency Virus-infected Cats - Uckun, Fatih M.; Waurzyniak, Barbara; Tibbles, Heather; Venkatachalam, Taracad K.; Erbeck, Doug (Arzneimittelforschung, 2006)
The pharmacokinetics and toxicity profile of stampidine (STAMP, DDE-113, HI-113, N-[p-(4-bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester, CAS 217178-62-6) were studied in beagle dogs and feline immunodeficiency virus-infected domestic cats. Therapeutic plasma concentrations of STAMP 3-4 logs higher than its IC50 value can be achieved after its p.o. administration to dogs as well as cats at the 100 mg/kg nontoxic dose level. In accordance with its safety profile in rodent species, a 4- to 7-week STAMP treatment course with twice daily administration of hard gelatin capsules containing 25-100 mg/kg (50-200 mg/kg/day) STAMP was very well-tolerated by dogs and cats at cumulative dose levels as high as 8.4 g/kg. Except for the sporadic occurrence of nausea and vomiting after its administration and elevation of serum ALT levels in some of the cats, STAMP therapy was not associated with any clinical or laboratory evidence of toxicity. No STAMP-related toxic lesions were found in any of the organs from STAMP-treated cats or dogs. These findings encourage the further development of stampidine for possible clinical use in HIV-infected persons.
Keywords: Anti-HIV agents; Antiretroviral therapy; N-[p-(4-Bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester; CAS 217178-62-6; DDE-113; HI-113; Stampidine, toxicity profile